A low-energy building under arctic conditions – a case study - Norling, Casper Roland; Rode, Carsten; Svendsen, Svend; Kragh, Jesper; Reimann, Gregers Peter (Taylor & Francis, 2006)
Greenland is a relatively small community with limited natural resources, which results in the necessity to import all supplies, including a big share of the energy. Because of this, it is important to decrease the energy consumption. This can be done by developing new construction technology with larger focus on energy efficiency. Therefore a low-energy house, located in Sisimiut, has been constructed. The low-energy house will be a forerunner for the development of new building element designs and technologies in Greenland. In the forthcoming years, the house will also be a base for scientific projects which will evaluate the design of the low-energy house including an assessment of the effect of the highly insulated building envelope, advanced windows and a ventilation system with heat recovery, all of which cuts the energy consumption of the building to half of what will be the requirement in the new Greenlandic building regulations.